1995
DOI: 10.1177/156482659501600114
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients and Some Anti-Nutrients in Horsegram (Macrotyloma Uniflorum (Lam.) Verdc.)

Abstract: Proximate nutrients, calcium, and some anti-nutrients in 16 varieties of whole horsegram and their dehulled seeds were estimated The protein, fat, and carbohydrate contents were higher in the dehulled samples than in the corresponding whole horsegram However, the moisture, fibre, ash, and calcium contents of the dehulled samples were lower. A significant portion of the anti-nutrients studied were removed by dehulling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 4 publications
3
26
1
Order By: Relevance
“…However, Yorgancilar and Bilgicli (2014) also observed a reduction in fat content of lupin after cooking and drying. Sudha et al (1995) found small reductions in the lipid content of germinated horse gram. El-Adawy (2002) observed significant reductions in lipid contents of chickpea subjected to boiling, autoclaving, and microwaving processes.…”
Section: Lipid Content and Composition Of Pulse Cropsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, Yorgancilar and Bilgicli (2014) also observed a reduction in fat content of lupin after cooking and drying. Sudha et al (1995) found small reductions in the lipid content of germinated horse gram. El-Adawy (2002) observed significant reductions in lipid contents of chickpea subjected to boiling, autoclaving, and microwaving processes.…”
Section: Lipid Content and Composition Of Pulse Cropsmentioning
confidence: 94%
“…Kalogeropoulos et al (2010) reported a range in the fiber content of 14 cooked pulses between 3.6% in white lupin and 11.7% in small white beans. Dehulling caused a 62% reduction in dietary fiber of horse gram (Sudha et al 1995) but only an 11% reduction in mung bean (Mubarak 2005). Boiled kidney beans had total dietary fiber content of 11%, whereas boiled mung beans contained slightly over 4% dietary fiber (Aldwairji et al 2014).…”
Section: Carbohydrate Content and Composition Of Pulse Cropsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is used as a vegetable in India and is known as the poor man's pulse crop in southern India. Previous studies showed that horse gram is a good source of proteins, carbohydrates, essential amino acids, and is an excellent source of iron and molybdenum (Bravo, Siddhuraju, & Saura-Calixto, 1999;Kadam & Salunkhe, 1985;Sudha, Mushtari Begum, Shambulingappa, & Babu, 1995). Horse gram also possesses many health beneficial components (Siddaraju & Manian, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…(2009) found 623–1240 mg oxalates in 100 g of dry matter. Sudha et al. (1995) reported that dehulled seeds of horse gram contained 38% less oxalates compared with whole seeds.…”
Section: Resultsmentioning
confidence: 99%